2016
DOI: 10.4103/0970-9290.191880
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported musculoskeletal pain among dentists in Visakhapatnam: A 12-month prevalence study

Abstract: Within the limits of the study, the prevalence of WRMSD among dentists in Visakhapatnam, especially involving the neck, hand, lower back, and shoulders, is high. Gender, age, height, and weight, BMI and experience were found to be related with musculoskeletal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…The regions most committed to musculoskeletal disorders were the neck, upper back, shoulders, wrists / hands and lower back, and similar findings were found in studies of dental professionals [14][15][16][17][19][20][21] . The dentist performs flexion and abduction of the shoulder to serve as a support base for the fine and precise movements performed with the hands, so the more overloaded regions by static muscular effort of these professionals are the neck, shoulder and lower back 10,15,21 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The regions most committed to musculoskeletal disorders were the neck, upper back, shoulders, wrists / hands and lower back, and similar findings were found in studies of dental professionals [14][15][16][17][19][20][21] . The dentist performs flexion and abduction of the shoulder to serve as a support base for the fine and precise movements performed with the hands, so the more overloaded regions by static muscular effort of these professionals are the neck, shoulder and lower back 10,15,21 .…”
Section: Discussionsupporting
confidence: 77%
“…In this study, the majority of respondents were female (63.8%), but this condition was not a risk factor for the presence of pain. Dentistry has shown a gradual increase in female workers in recent years 11,[14][15][16][17][18] . The correlation between gender and pain becomes more evident with each passing year, this factor must be the mechanical overload caused by double shifts to which women are subjected, thus establishing an association between the female gender and musculoskeletal disorders 11,15,19 .…”
Section: Discussionmentioning
confidence: 99%
“…3 In the clinic, positioning the operator's chair correctly and making sure that it has good lumbar support has shown to be effective in preventing MSP. Practicing proper techniques at work with a trained assistant 14 and keeping the most frequently used equipment 50 cm from the operator are also recommended. 3 Moreover, studies have shown that the use of magnification is associated with decreased neck and lower back pain as it allows the dentist to maintain a proper posture.…”
Section: Discussionmentioning
confidence: 99%
“…26% of dentists experience numbness in hands after finishing work, 18% admits that they feel sickness, imbalance or dizziness after work [8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%